Lipopolysaccharide alters CEBPβ signaling and reduces estradiol production in bovine granulosa cells - Mackenzie J. Dickson; I. Martin Sheldon; John J. Bromfield (CABI Agriculture and Bioscience)
Abstract Background Bacterial infection of the uterus in postpartum dairy cows limits ovarian follicle growth, reduces blood estradiol concentrations, and leads to accumulation of bacterial lipopolysaccharide (LPS) in ovarian follicular fluid. Although treating granulosa cells with LPS in vitro decreases the expression of the estradiol synthesis enzyme CYP19A1 and reduces estradiol secretion, the molecular mechanisms are unclear. The transcription factor CCAAT enhancer binding protein beta (CEBPβ) not only facilitates the transcription of LPS regulated cytokines, but also binds to the promoter region of CYP19A1 in humans, mice, and buffalo. We hypothesized that LPS alters CEBPβ signaling to reduce CYP19A1 expression, resulting in decreased estradiol secretion. Methods Bovine granulosa cells were isolated from small/medium or large follicles and treated with LPS in the presence of FSH and androstenedione for up to 24 h. Results Treatment with LPS increased CXCL8 and IL6 gene expression and reduced estradiol secretion in granulosa cells from both small/medium and large follicles. However, LPS only reduced CYP19A1 expression in granulosa cells from large follicles. Treatment with LPS increased CEBPB expression and reduced CEBPβ nuclear localization in granulosa cells from small/medium follicles, but not granulosa cells from large follicles. Conclusions Although LPS reduces estradiol synthesis in bovine granulosa cells, the effects of LPS on CYP19A1 and CEBPβ are dependent on follicle size.